Productive and biochemical responses of durum wheat to UV filtration. (13th March 2019) - Grifoni, Daniele; Napoli, Marco; Sabatini, Francesco; Orlandini, Simone; Mancini, Marco; Zipoli, Gaetano; Dalla Marta, Anna
Abstract: A UV exclusion experiment was conducted on durum wheat ( Triticum durum Desf. var. Claudio) grown in pots. Plants were grown under three different radiative treatments in greenhouses covered with plastic filters: Teflon, transparent to the entire region of natural UV‐visible sunlight (TEF); polyester, transparent above 312 nm (MYL, excluding UVB) and Lee, transparent above 400 nm (LEE, excluding both UVA and UVB). Analyses have been carried out to determine the concentration of photosynthetic pigments in leaves, UV‐absorbing compounds, nitrogen and carbon in leaves, culms and spikes and proteins and gluten in grains. In particular, plants grown under UV exclusion showed a reduction in protein and dry gluten content (consequently without variation in the ratio dry gluten/protein), but at the same time, a significant increase of gluten index, which is a parameter to define the quality of gluten, was observed. The results highlighted the influence played by UV radiation on some biochemical parameters, mainly UV‐absorbing compounds, leaf nitrogen and grain protein characteristics of durum wheat cultivated under Mediterranean conditions. In particular, natural level of UV in the Mediterranean improves the characteristics of durum wheat flour important for pasta production (high dry gluten level), while the UV exclusion could improve characteristics of flour important for bread production (high gluten index).